Crisis in Early Religion
VI, 198 p. 1 illus.
Keywords: Religion is closely linked to social development as it often serves as the ideological fundament of a society and one of the foremost expressions of its culture. The articles in this volume are devoted to the study of religious crisis in Anqituity and deal with these pheonomena in the Ancient Near East, Rome, Greece, China and India. The Editors Dr. Mait Kõiv is the associate professor of Ancient History in the University of Tartu, with the main research field in the Ancient Greek history. Dr. Märt Läänemets is an Orientalist-Sinologist focusing on the field of history of thought and religion in China, classical Chinese and Buddhist texts; he is the President of the Estonian Oriental Society. PD Dr. Kerstin Droß-Krüpe is a historian of ancient history and currently works as an Akademische Oberrätin at the Ruhr-University Bochum. Dr. Sebastian Fink is Senior Scientist at the Institute for Ancient History and Ancient Near Eastern Studies at the University of Innsbruck.